Acid or bifunctional mechanism in paraffin isomerization reaction on Pt/SO42−−ZrO2 and Pt/WO3−ZrO2 catalysts - Yori, Juan Carlos (2000)
At low temperature (300°C) the isomerization of n-C4H10 on Pt/SZ occurs only by a monofunctional acid mechanism. It is necessary to increase the temperature to produce the amount of olefins requiered for the bifunctional mechanism because of thermodynamic limitations and the decrease of metallic function acvtivity of Pt due to support interactions. Pt is less affected on Pt/WZ, presenting high hydrogenolysis activity. The isomerization of n-C7H16 can proceed at low temperatures by a bifunctional mechanism because due to the easy dehydrogenation to n-C7H14 a very small fraction of metallic function is enough.